Anode-resistant anode-lacking-gas reverse-pole high-temperature anode electrocatalyst, and preparation method and application thereof

CN116266630BActive Publication Date: 2026-10-16DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111539126.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2026-10-16
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

[0004]本申请针对高温电解质膜燃料电池在阳极欠气或低计量比进料条件下易发生反极的问题,申请了一种新型耐阳极欠气反极阳极电催化剂

Benefits of technology

[0044] Because of the palladium membrane layer, under the operating temperature (150-200 degrees Celsius) of high-temperature polymer electrolyte membrane fuel cells, metallic palladium has a hydrogen storage and release mechanism. Under the condition of insufficient anode gas, online hydrogen release can be realized to alleviate the occurrence of reverse polarity, greatly improve the reliability of membrane electrode, and improve the fuel utilization efficiency of membrane electrode. At the same time, the preparation process of this method is simple and can be carried out in batches, which has high application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116266630B_ABST
    Figure CN116266630B_ABST
Patent Text Reader

Abstract

The application discloses an anode-resistant and reverse-pole high-temperature anode electrocatalyst, a preparation method and application thereof. The anode-resistant and reverse-pole high-temperature anode electrocatalyst comprises a carbon carrier and platinum nanoparticles loaded on the surface of the carbon carrier; the surface of the carbon carrier is coated with a palladium elemental layer; the thickness of the palladium elemental layer is 1-10 nanometers; the mass ratio of the palladium element to the carbon carrier is 1:2-2:3; the particle size of the platinum nanoparticles is 3-5 nanometers; and the mass ratio of the platinum element in the platinum nanoparticles to the carbon carrier is 1:2-2:1. Because of the palladium film layer, under the operating temperature (150-200 DEG C) of a high-temperature polymer electrolyte membrane fuel cell, the metal palladium has a hydrogen storage and hydrogen release mechanism, the on-line hydrogen release can be realized under the anode gas deficiency condition, the occurrence of the reverse-pole phenomenon is relieved, the membrane electrode reliability is greatly improved, the membrane electrode fuel utilization efficiency is improved, the preparation method is simple, the batch method can be realized, and the application value is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of fuel cell technology, specifically relating to a high-temperature anolyte resistant to under-gas reverse electrode, its preparation method, and its application. Background Technology

[0002] High-temperature polymeric electrolyte membrane fuel cells (PEMFCs) based on phosphoric acid exhibit higher CO tolerance compared to lower-temperature PEMFCs, with the maximum CO tolerance concentration increasing from below 10 ppm to around 3%. This allows for the direct utilization of reformed gases from fuels such as methanol, ethanol, gasoline, diesel, and methane, significantly simplifying the complexity of fuel cell systems and enabling online reforming of liquid fuels for hydrogen power generation. This technology holds promise for applications in combined cooling, heating, and power (CCHP), range-extended electric power supplies, and portable backup power sources. However, the introduction of liquid phosphoric acid significantly increases the material transport resistance of the porous electrodes in high-temperature PEMFCs. For hydrogen transport on the anode side, compared to the relatively fast-paced hydrogen oxidation reaction (HOR), hydrogen transport in the membrane electrode becomes the rate-determining step in the electrode process under low hydrogen concentration (40-70%) conditions. Furthermore, to ensure system efficiency, high anode fuel utilization efficiency is a crucial solution for high-temperature PEMFC systems. Anode inlet metering ratios are often below 1.4 or even 1.2, further placing higher demands on anode material transport. Under conditions of limited mass transport, low stoichiometric inlet gas can lead to various technical problems for the membrane electrode assembly (MEA). First, at the operating point, reactants cannot reach the active sites in time. Due to the oxidation reaction of carbon materials in the stack's series electrodes, this can cause reverse polarity of the MEA, and at excessively high potentials, it can even lead to MEA perforation and failure. Second, limited hydrogen mass transfer can easily lead to the adsorption and accumulation of poisonous species such as CO in the phosphoric acid electrolyte, resulting in a decline in MEA performance and stability. Therefore, improving the MEA's anti-reverse polarity capability under low stoichiometric inlet gas conditions is crucial for the stable and reliable operation of high-temperature polymer electrolyte membrane fuel cell systems.

[0003] Existing anti-reverse polarization strategies for membrane electrodes (MEAs) primarily rely on two technical approaches. First, optimizing the flow field and gas diffusion layer structure improves the hydrophobicity of the bipolar plate and gas diffusion electrode, enhancing mass transport and reducing the wettability of phosphoric acid on the electrode, effectively mitigating reverse polarization caused by insufficient gas under low-stoichiometric feed conditions. Second, leveraging the charge-discharge characteristics of pseudocapacitive materials such as ruthenium oxide and cerium oxide can mitigate rapid voltage fluctuations under insufficient gas conditions, reducing overpotential corrosion of the MEA due to insufficient gas. While these approaches alleviate the reverse polarization phenomenon to some extent, they do not fundamentally solve the anode insufficient gas problem at the electrode process level. Therefore, these approaches are difficult to apply effectively in fuel cell stacks and systems. Summary of the Invention

[0004] This application addresses the problem of reverse polarity easily occurring in high-temperature electrolyte membrane fuel cells under conditions of anode undergassing or low metering ratio feed, and proposes a novel anode electrocatalyst resistant to anode undergassing and reverse polarity.

[0005] According to one aspect of this application, a high-temperature anodic electrocatalyst resistant to anode undergassing is provided, comprising a carbon support and platinum nanoparticles supported on the surface of the carbon support.

[0006] The surface of the carbon support is coated with a palladium elemental layer;

[0007] The thickness of the palladium monolayer is 1–10 nanometers;

[0008] The mass ratio of palladium to carbon support is 1:2 to 2:3.

[0009] The platinum nanoparticles have a particle size of 3–5 nanometers.

[0010] The mass ratio of platinum to carbon support in the platinum nanoparticles is 1:2 to 2:1.

[0011] The carbon support is selected from at least one of activated carbon, carbon nanotubes, or graphene.

[0012] According to another aspect of this application, a method for preparing the above-mentioned resistant high-temperature anolyte electrocatalyst with anode undergassing is provided, comprising at least the following steps:

[0013] (1) The carbon support is immersed in the plating solution, reacted I, and dried I to obtain a carbon support with a palladium layer on the surface.

[0014] (2) The carbon support with palladium layer on the surface obtained in (1) is immersed in ethylene glycol solution containing platinum source, reaction II, drying II, to obtain the anolyte resistant high temperature anolyte electrocatalyst with under-gas reverse electrode.

[0015] In (1), the plating solution contains elemental palladium and a reducing agent;

[0016] The reducing agent is selected from at least one of hydrazine hydrate, sodium borohydride, or ascorbic acid;

[0017] The palladium plating solution contains 0.05 to 1 mole of palladium per liter;

[0018] The content of the reducing agent is 0.1 to 3 mol per liter;

[0019] The temperature of reaction I is 25–80°C;

[0020] Preferably, the temperature of reaction I is 40–80°C;

[0021] The reaction time for reaction I is 1 to 20 minutes;

[0022] Preferably, the reaction time for step I is 1 to 10 minutes;

[0023] The temperature of the drying process is 30–80 degrees Celsius.

[0024] The drying time is 2 to 4 hours.

[0025] The platinum source is selected from at least one of chloroplatinic acid, platinum acetate, or dinitrosodiammineplatinum.

[0026] The platinum source in the ethylene glycol solution containing the platinum source is 0.5 to 50 mmol per liter.

[0027] The carbon support with a palladium layer on its surface obtained in (1) and the ethylene glycol solution containing a platinum source have a platinum source content of 5-100 mg / ml.

[0028] The temperature of reaction II is 100–160°C;

[0029] The reaction time for reaction II is 2 to 6 hours;

[0030] The temperature of the drying II process is 30–80 degrees Celsius;

[0031] The drying time for step II is 0.5 to 5 hours.

[0032] According to another aspect of this application, a high-temperature polymer electrolyte membrane is provided, containing the above-described resistant high-temperature anodic electrocatalyst for anodic undergassing or the resistant high-temperature anodic electrocatalyst for anodic undergassing prepared by the above-described preparation method.

[0033] According to another aspect of this application, a high-temperature polymer electrolyte membrane fuel cell is provided, employing the aforementioned high-temperature polymer electrolyte membrane.

[0034] Specifically, the catalyst has a composite structure, consisting of three parts: a carbon support, a palladium nanoparticle coating, and platinum nanoparticles.

[0035] The carbon support is one of activated carbon, carbon nanotubes, or graphene.

[0036] The palladium coating layer has a thickness of 1–10 nanometers and a mass ratio of 1:1 to 2:1 with the carbon support.

[0037] The platinum nanoparticles have a particle size of 3 to 5 nanometers and a mass ratio of 1:2 to 2:1 with the carbon support.

[0038] The preparation process of this catalyst includes the following steps:

[0039] a. Carbon support pretreatment: A certain mass of carbon support is dispersed in concentrated nitric acid and refluxed at 60 degrees Celsius for 2-4 hours. After cooling, it is filtered and washed with deionized water until no nitrate ions are detected in the filtrate. After drying, it is ready for use.

[0040] b. Immerse the treated carbon support in the palladium core solution of the commercial palladium plating solution, stir thoroughly with ultrasonication, and continue stirring at 40-80 degrees Celsius for 1-4 hours. After filtration, wash with deionized water 2-4 times. Then, immerse the filtered carbon support in the reducing solution of the commercial palladium plating solution and react at room temperature for 1-10 minutes. After filtration, wash with deionized water 2-4 times. Then, immerse it in the palladium plating solution of the commercial palladium plating solution and react at room temperature for 1-20 minutes. After filtration, wash with deionized water until no chloride ions are detected in the filtrate. Dry in a vacuum oven at 50 degrees Celsius for 2-4 hours for later use.

[0041] c. Disperse the above-mentioned palladium-coated carbon support in ethylene glycol at a concentration of 5-100 mg / mL, and add a certain amount of chloroplatinic acid. After dissolving and homogenizing, heat to 100-160°C and stir continuously for 1-4 hours. Add a sodium hydroxide solution in ethylene glycol (concentration of 1-2 mol / L) dropwise until the pH of the solution is between 9-14. Continue stirring for another 1-2 hours. Filter while hot and wash with plenty of deionized water until chloride ions are undetectable in the filtrate. Dry the filter cake in a vacuum oven for 2-4 hours, grind and disperse it for later use.

[0042] d. The prepared anode electrocatalyst can be used to perform various performance tests by rotating disk electrodes and assembling high-temperature polymer electrolyte membrane fuel cells.

[0043] Compared with existing technologies, the advantages of this application are:

[0044] Because of the palladium membrane layer, under the operating temperature (150-200 degrees Celsius) of high-temperature polymer electrolyte membrane fuel cells, metallic palladium has a hydrogen storage and release mechanism. Under the condition of insufficient anode gas, online hydrogen release can be realized to alleviate the occurrence of reverse polarity, greatly improve the reliability of membrane electrode, and improve the fuel utilization efficiency of membrane electrode. At the same time, the preparation process of this method is simple and can be carried out in batches, which has high application value.

[0045] In view of the problems existing in the prior art, and based on the hydrogen storage / release characteristics of metal compounds under specific temperature conditions, this application realizes the technical mechanism of in-situ hydrogen release when the gas is insufficient, which is expected to fundamentally solve the problem of reverse polarity when the membrane electrode is under-gas. Attached Figure Description

[0046] Figure 1The results of the hydroxide leaching performance and carbon monoxide dissolution test of the anolyte electrocatalyst prepared in Example 1 of this application are shown. a) shows the hydroxide reaction test result; b) shows the carbon monoxide dissolution test result.

[0047] Figure 2 The results of the membrane electrode performance test (a) and the reverse electrode performance test under the undergassing condition are shown for the anode electrocatalysts assembled in Example 1 and Comparative Example 1 of this application. Detailed Implementation

[0048] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0049] Example 1

[0050] a. Carbon carrier pretreatment: A certain mass of activated carbon is dispersed in concentrated nitric acid and refluxed at 60 degrees Celsius for 2 hours. After cooling, it is filtered and washed with deionized water until no nitrate ions are detected in the filtrate. After drying, it is ready for use.

[0051] b. The activated carbon treated above is immersed in a commercial palladium plating solution containing sodium tetrachloropalladium, and thoroughly ultrasonically stirred until homogeneous. The mixture is then continuously stirred at 60°C for 2 hours. After filtration, it is washed 2-4 times with deionized water. Subsequently, the filtered carbon carrier is immersed in a commercial palladium plating reducing solution containing hydrazine hydrate and reacted at room temperature for 5 minutes. After filtration, it is washed 2-4 times with deionized water. Then, it is immersed in a palladium plating solution containing commercial palladium plating solution and reacted at room temperature for 10 minutes. After filtration, it is washed with deionized water until no chloride ions are detected in the filtrate. The carbon is then dried in a vacuum oven at 50°C for 2 hours for later use. The mass ratio of palladium to carbon is 1:1.

[0052] c. Disperse the above-mentioned palladium-coated activated carbon in ethylene glycol at a concentration of 10 mg / mL, and add a certain amount of chloroplatinic acid, wherein the platinum-carbon mass ratio is 1:2. After dissolving and homogenizing, heat to 120°C and stir continuously for 2 hours. Add a sodium hydroxide solution in ethylene glycol (concentration of 1 mol / L) dropwise until the pH of the solution is about 13. Continue stirring for another 1-2 hours. Filter while hot and wash with a large amount of deionized water until no chloride ions are detected in the filtrate. Dry the filter cake in a vacuum oven for 2 hours, grind and disperse it for later use.

[0053] d. The prepared anode electrocatalyst can be subjected to various performance tests by rotating disk electrodes and assembling a high-temperature polymer electrolyte membrane fuel cell. The battery assembly adopts a polybenzimidazole-doped phosphoric acid electrolyte membrane. The prepared anode electrocatalyst is sprayed on the surface of the gas diffusion layer. The test conditions are: temperature 160 degrees Celsius, hydrogen gas with a 1.1 times stoichiometric ratio is introduced into the anode, and air gas with a 3 times stoichiometric ratio is introduced into the cathode.

[0054] Figure 1The results of the anolyte electrocatalyst prepared in Example 1 of this application show its hydrogenation performance and carbon monoxide dissolution test results. The results show that the catalyst has a high catalytic activity with an overpotential of 18 mV at 1 mA / cm² during the catalytic hydrogenation reaction. The carbon monoxide dissolution results show that the catalyst has an electrochemically active specific surface area of ​​81.7 m² / g platinum, which indicates a high utilization rate of precious metals.

[0055] Comparative Example 1

[0056] The comparative example is a platinum-supported activated carbon catalyst material without a palladium shell coating, and its preparation process is as follows:

[0057] a. Carbon carrier pretreatment: A certain mass of activated carbon is dispersed in concentrated nitric acid and refluxed at 60 degrees Celsius for 2 hours. After cooling, it is filtered and washed with deionized water until no nitrate ions are detected in the filtrate. After drying, it is ready for use.

[0058] b. Disperse the above-treated activated carbon in ethylene glycol at a concentration of 10 mg / mL, and add a certain amount of chloroplatinic acid, wherein the platinum-carbon mass ratio is 1:2. After dissolving and homogenizing, heat to 120°C and stir continuously for 2 hours. Add ethylene glycol solution of sodium hydroxide (concentration of 1 mol / L) dropwise until the pH of the solution is about 13. Continue stirring for another 1-2 hours. Filter while hot and wash with a large amount of deionized water until chloride ions are undetectable in the filtrate. Dry the filter cake in a vacuum oven for 2 hours, grind and disperse it for later use.

[0059] c. The prepared anode electrocatalyst can be subjected to various performance tests by rotating disk electrodes and assembling a high-temperature polymer electrolyte membrane fuel cell. The battery assembly adopts a polybenzimidazole-doped phosphoric acid electrolyte membrane. The prepared anode electrocatalyst is sprayed on the surface of the gas diffusion layer. The test conditions are a temperature of 160 degrees Celsius, hydrogen gas with a 1.1-fold stoichiometric ratio is introduced into the anode, and air gas with a 3-fold stoichiometric ratio is introduced into the cathode.

[0060] Example 2

[0061] The preparation process of this anode electrocatalyst includes the following steps:

[0062] a. Carbon support pretreatment: A certain mass of carbon nanotubes is dispersed in concentrated nitric acid and refluxed at 60 degrees Celsius for 2 hours. After cooling, the solution is filtered and washed with deionized water until no nitrate ions are detected in the filtrate. The solution is then dried for later use.

[0063] b. Immerse the treated carbon nanotubes in a commercial palladium plating solution containing sodium tetrachloropalladium, stir thoroughly with ultrasonic stirring, and continue stirring at 40 degrees Celsius for 2 hours. After filtration, wash with deionized water 2-4 times. Then, immerse the filtered carbon nanotubes in a commercial palladium plating reducing solution containing sodium borohydride and react at room temperature for 5 minutes. After filtration, wash with deionized water 2-4 times. Then, immerse them in the palladium plating solution containing the commercial palladium plating solution and react at room temperature for 10 minutes. After filtration, wash with deionized water until no chloride ions are detected in the filtrate. Dry in a vacuum oven at 50 degrees Celsius for 2 hours for later use. The mass ratio of palladium to carbon is 2:1.

[0064] c. Disperse the above-mentioned palladium-coated carbon nanotubes in ethylene glycol at a concentration of 1 mg / mL, and add a certain amount of chloroplatinic acid, wherein the platinum-carbon mass ratio is 1:1. After dissolving and homogenizing, heat to 140°C and stir continuously for 2 hours. Add a sodium hydroxide solution in ethylene glycol (concentration of 2 mol / L) dropwise until the pH of the solution is about 11. Continue stirring for another 1-2 hours. Filter while hot and wash with a large amount of deionized water until no chloride ions are detected in the filtrate. Dry the filter cake in a vacuum oven for 2 hours, grind and disperse it for later use.

[0065] d. The prepared anode electrocatalyst can be subjected to various performance tests by rotating disk electrodes and assembling a high-temperature polymer electrolyte membrane fuel cell. The battery assembly adopts a polybenzimidazole-doped phosphoric acid electrolyte membrane. The prepared anode electrocatalyst is sprayed on the surface of the gas diffusion layer. The test conditions are: temperature 160 degrees Celsius, hydrogen gas with a 1.1 times stoichiometric ratio is introduced into the anode, and air gas with a 3 times stoichiometric ratio is introduced into the cathode.

[0066] Figure 2 The figures show the performance test results (a) and the reverse polarity test results under sub-gas conditions of the membrane electrodes assembled with the anode electrocatalysts of Example 1 and Comparative Example 1 described in this application. As shown in the figure, the performance of the membrane electrode prepared in Example 1 is not significantly different from that of the membrane electrode of Comparative Example 1 (conventional structure). Under sub-gas conditions, the reverse polarity time of Example 1 is significantly extended by 40% compared with that of Comparative Example 1, indicating that the anode electrocatalyst has excellent anti-reverse polarity ability.

[0067] Example 3

[0068] The preparation process of this anode electrocatalyst includes the following steps:

[0069] a. Carbon support pretreatment: A certain mass of graphene is dispersed in concentrated nitric acid and refluxed at 60 degrees Celsius for 2 hours. After cooling, it is filtered and washed with deionized water until no nitrate ions are detected in the filtrate. After drying, it is ready for use.

[0070] b. Immerse the above-treated graphene in a commercial palladium plating solution containing sodium tetrachloropalladium, stir thoroughly with ultrasonic stirring, and continue stirring at 80 degrees Celsius for 2 hours. After filtration, wash with deionized water 2-4 times. Then, immerse the filtered graphene in a commercial palladium plating reducing solution containing ascorbic acid and react at room temperature for 5 minutes. After filtration, wash with deionized water 2-4 times. Then, immerse it in the palladium plating solution containing the commercial palladium plating solution and react at room temperature for 10 minutes. After filtration, wash with deionized water until no chloride ions are detected in the filtrate. Dry in a vacuum oven at 50 degrees Celsius for 2 hours for later use. The mass ratio of palladium to carbon is 1:1.

[0071] c. Disperse the above-mentioned graphene coated with palladium film in ethylene glycol at a concentration of 10 mg / mL, and add a certain amount of chloroplatinic acid, wherein the platinum-carbon mass ratio is 2:1. After dissolving and homogenizing, heat to 160 degrees Celsius and stir continuously for 2 hours. Add ethylene glycol solution of sodium hydroxide (concentration of 1 mol / L) dropwise until the pH of the solution is about 12. Continue stirring for another 1-2 hours. Filter while hot and wash with a large amount of deionized water until chloride ions are not detected in the filtrate. Dry the filter cake in a vacuum oven for 2 hours, grind and disperse it for later use.

[0072] d. The prepared anode electrocatalyst can be subjected to various performance tests by rotating disk electrodes and assembling a high-temperature polymer electrolyte membrane fuel cell. The battery assembly adopts a polybenzimidazole-doped phosphoric acid electrolyte membrane. The prepared anode electrocatalyst is sprayed on the surface of the gas diffusion layer. The test conditions are: temperature 160 degrees Celsius, hydrogen gas with a 1.1 times stoichiometric ratio is introduced into the anode, and air gas with a 3 times stoichiometric ratio is introduced into the cathode.

[0073] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high-temperature anodic electrocatalyst, characterized in that, Including carriers and platinum nanoparticles; The surface of the carrier is coated with a palladium elemental layer; the coating may be a full coating or a partial coating. The platinum nanoparticles are loaded on the surface of the carrier; The thickness of the palladium monolayer is 1~10 nanometers; The mass ratio of palladium to carbon support is 1:2 to 2:

3. The platinum nanoparticles have a particle size of 3-5 nanometers; The mass ratio of platinum to carbon support in the platinum nanoparticles is 1:2 to 2:

1. The preparation method of the high-temperature anolyte includes the following steps: (1) The carrier is immersed in palladium plating solution, reaction I, and dried I to obtain a carrier with a palladium elemental layer on the surface; (2) The support with a palladium layer on its surface obtained in (1) is immersed in an ethylene glycol solution containing a platinum source, reaction II is carried out, and then dried to obtain the high-temperature anodic electrocatalyst. The electrocatalyst is used in a high-temperature polymer electrolyte membrane fuel cell, and under operating temperature conditions of 150~200 degrees Celsius, the palladium elemental layer has a hydrogen storage and release mechanism, which is used to realize online hydrogen release under anode under insufficient gas conditions, thereby alleviating the occurrence of reverse polarity.

2. The high-temperature anolyte electrocatalyst according to claim 1, characterized in that, The carrier is selected from at least one of activated carbon, carbon nanotubes, or graphene.

3. A method for preparing the high-temperature anolyte electrocatalyst according to claim 1, characterized in that, At least the following steps are included: (1) The carrier is immersed in palladium plating solution, reaction I, and dried I to obtain a carrier with a palladium elemental layer on the surface; (2) The support with palladium layer on the surface obtained in (1) is immersed in ethylene glycol solution containing platinum source, reaction II, and dried to obtain the high temperature anodic electrocatalyst.

4. The preparation method according to claim 3, characterized in that, (1) The palladium plating solution contains elemental palladium and a reducing agent; The reducing agent is selected from at least one of hydrazine hydrate, sodium borohydride, or ascorbic acid; The palladium plating solution contains 0.05 to 1 mole of palladium per liter; The content of the reducing agent is 0.1~3 mol per liter; The temperature of reaction I is 25~80℃.

5. The preparation method according to claim 3, characterized in that, The temperature of reaction I is 40~80℃; The reaction time for reaction I is 1 to 20 minutes.

6. The preparation method according to claim 3, characterized in that, The reaction time for reaction I is 1 to 10 minutes; The drying temperature I is 30~80 degrees Celsius; The drying time for step I is 2 to 4 hours.

7. The preparation method according to claim 3, characterized in that, In (2), the platinum source is selected from at least one of chloroplatinic acid, platinum acetate, or dinitrosodiammineplatinum; The platinum source in the ethylene glycol solution containing the platinum source is 0.5 to 50 mmol per liter. The carbon support with a palladium layer on its surface obtained in (1) and the ethylene glycol solution containing a platinum source have a platinum source content of 5~100 mg / ml; The temperature of reaction II is 100~160℃; The reaction time for reaction II is 2-6 hours; The temperature of the drying II process is 30-80 degrees Celsius; The drying time for step II is 0.5 to 5 hours.

8. A high-temperature polymer electrolyte membrane, characterized in that, The high-temperature anodic electrocatalyst comprising the high-temperature anodic electrocatalyst according to claim 1 or 2, or the high-temperature anodic electrocatalyst prepared by the preparation method according to any one of claims 3 to 7.

9. A high-temperature polymer electrolyte membrane fuel cell, characterized in that, The high-temperature polymer electrolyte membrane described in claim 8 is used.

Citation Information

Patent Citations

  • Preparation method of Pd(alpha)Pt fuel cell catalyst for direct formic acid fuel cell

    CN103143348A